2020
DOI: 10.1021/acsami.0c09689
|View full text |Cite
|
Sign up to set email alerts
|

MOF-Derived Bimetallic CoFe-PBA Composites as Highly Selective and Sensitive Electrochemical Sensors for Hydrogen Peroxide and Nonenzymatic Glucose in Human Serum

Abstract: The fabrication of two-dimensional (2D) metal−organic frameworks (MOFs) and Prussian blue analogues (PBAs) combines the advantages of 2D materials, MOFs and PBAs, resolving the poor electronic conductivity and slow diffusion of MOF materials for electrochemical applications. In this work, 2D leaflike zeolitic imidazolate frameworks (Co-ZIF and Fe-ZIF) as sacrificial templates are in situ converted into PBAs, realizing the successful fabrication of PBA/ZIF nanocomposites on nickel foam (NF), namely, CoCo-PBA/Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 62 publications
1
61
0
Order By: Relevance
“…In previous work, it has been demonstrated that the hollow Co 3 O 4 nanostructures obtained from the cobalt‐based zeolite imidazolate framework (ZIF‐67) calcined in oxygen atmosphere exhibit rough surface, rich microporous structure and excellent biocompatibility, but it also shows low electrical conductivity and poor structural robustness during electrolysis [26,27] . Therefore, MOF‐derived nanomaterials are expected to show an enhanced catalytic performance with long‐term stability for glucose oxidation [28–31] …”
Section: Figurementioning
confidence: 99%
“…In previous work, it has been demonstrated that the hollow Co 3 O 4 nanostructures obtained from the cobalt‐based zeolite imidazolate framework (ZIF‐67) calcined in oxygen atmosphere exhibit rough surface, rich microporous structure and excellent biocompatibility, but it also shows low electrical conductivity and poor structural robustness during electrolysis [26,27] . Therefore, MOF‐derived nanomaterials are expected to show an enhanced catalytic performance with long‐term stability for glucose oxidation [28–31] …”
Section: Figurementioning
confidence: 99%
“…MOFs are typically produced by solution mixture from room temperature to 250 °C at ambient pressure, with reaction time from a couple of minutes to several days. Due to the presence of the organic and inorganic moieties in their frameworks, they were extensively investigated in several technological applications such as gas adsorption and separation [57][58][59], electrocatalysis [17-19, 60, 61], chemical sensing [62][63][64], biomedical applications [64,65], and proton conduction [66,67]. Importantly, owing to the presence of the organic and inorganic counterparts in their composition, MOFs present numerous application chances in catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Ever since the conception of nanocrystalline materials by Rozlin in 2012, the CoFe alloy found in magnetic materials has presented excellent soft magnetic properties, categorized by high saturation magnetization (Ms) and a high Curie temperature (T C ) [1]. This topic has continued to attract the attention of scholars researching CoFe material, which can be applied to magnetic equipment for sensor, actuator, and read-write recorder applications [2][3][4][5][6]. The CoFe matrix with magnetic properties combines with boron (B) to form CoFeB material, which is a soft magnetic material that is applied widely to spin electronic devices.…”
Section: Introductionmentioning
confidence: 99%